RESPONS PADI SAWAH TERHADAP WAKTU PENGOLAHAN TANAH DAN JARAK TANAM BERBEDA DALAM SISTEM TANAM LEGOWO - Rizal, Rizal (JSTT, 2016)
This research conducted in the area of paddy fields Maranatha village, Sigi Sigi Biromaru Sub-district of Central Sulawesi. Held from December 2011 to March 2012. Research objectives get the right soil processing time towards growth and yield of rice plant, get the right planting distance in improving growth and yield of rice plant and get the right planting distance at any time of soil processing. This research is conducted in the form of a field experiment in rows with two separate Grid Design factors. As the main plot a time processing soil (P), which consists of two equal i.e. processing the soil 6 days before the planting (P1), and processing the soil of the 12 days before the planting (P2). As the son of harvesting is the distance (J) consisting of six equal i.e. 20 cm x 10 cm legowo 40 cm (J1), 20 cm x 15 cm legowo 40 cm (J2), 20 cm x 20 cm legowo 40 cm (J3), 20 cm x 15 cm legowo 30 cm (J4), 20 cm x 20 cm legowo 30 cm (J5) and 20 cm x 20 cm. The research results show the processing soil of the 12 days before planting accelerate planting flowering (73.90, off the day after a plant), produce of rice each more (147,46 panicle seeds-1), and dry milled of rice yield per hectare was higher (6,065 ton ha-1). The implementation of planting distance pattern 20 cm x 15 cm legowo 30 cm produce of rice dry grind higher (6,568 ton ha-1). The implementation of planting distance pattern 20 cm x 20 cm legowo 40 cm with 12 day processing soil before planting produces tillers (25,90 panicle clump-1), longer panicle (27,06 cm), more productive tiller (14,63 panicle grove-1) and less percentage empty of rice (9,48%).